Agrimonia eupatoria L. and Cynara cardunculus L. Water Infusions: Comparison of Anti-Diabetic Activities - Anika Kuczmannová; Andrea Balažová; Eva Račanská; Miroslava Kameníková; Silvia Fialová; Jaroslav Majerník; Milan Nagy; Peter Gál; Pavel Mučaji (Molecules, 2016)
Diabetes mellitus (DM) is frequently diagnosed at a time when patients already suffer from several cardiovascular complications. Our previously published data (Molecules 201520 (11): 20538-50) on the anti-oxidative properties of Agrimonia eupatoria L. (AE) and Cynara cardunculus L. (CC) prompted us to extend the available evidence on their possible protective activities on selected DM-related parameters in a streptozotocin-induced DM rat model and in a series of in vitro experiments. Male rats were divided into four groups: control group, untreated diabetic group, AE and CC treated diabetic groups. During a five-week period, changes in blood glucose and body weight were monitored. Then, rats were sacrificed and subjected to the assessment of changes in the reactivity of aortas and measurement of butyrylcholinesterase activity. To complete the panel of experiments, α-glucosidase activity was assessed in vitro. Our results demonstrate that both tested extracts exert similar anti-diabetic activities. However, better anti-oxidant activity of the A. eupatoria extract indicates its higher clinical potential in the prevention and/or adjuvant therapy of developing cardiovascular complications related to DM and diseases associated with oxidative stress.